PROPUESTA DE CREACIÓN DE UNA EMPRESA PARA LA DISTRIBUCIÓN DE PRODUCTOS DE PRIMERA NECESIDAD, EN LA PARROQUIA SAN CARLOS, APLICANDO LOGÍSTICA DE SERVICIO. - Hernández Montoya, Wilter Reinaldo (2023)
The processes are important due to the importance they have for the requirements of implementing a logistics of distribution services for essential products in the San Carlos parish of the Quevedo canton, applying route, time and distance optimization techniques. The procedure of this investigation involves identifying and obtaining the necessary resources to carry out a competitive project compared to current market offers. For the collection of information, a survey was carried out directed to the sample of the estimated population of the parish, managing to know the needs of the clients and the improvements that can be optimized in the service.